Complete Remission of Locally Advanced Penile Squamous Cell Carcinoma after Multimodality Treatment - Meng, Yifan (Rare Tumors, 2016)
Treatment of locally advanced penile squamous cell carcinoma (pSCC) remains highly controversial secondary to disease rarity and lack of prospective randomized controlled trials. The current mainstays of care are multi-modality treatment with neoadjuvant chemotherapy and surgery. However, clinicians often have difficulty making recommendations for patients unable to tolerate chemotherapy or surgery due to scarcity of data to guide clinical decision-making. We report two cases of locally advanced pSCC that achieved complete remission after treatment with cisplatin-based neoadjuvant chemotherapy and surgery in one case, and concurrent cisplatin chemoradiation in a second, supporting the use of chemotherapy as part of first-line multimodal therapy. We also discuss additional treatment options for patients unable to tolerate traditional chemotherapy regimens.